Augmented reality : unboxing tech's next big thing - Pesce, Mark, ....- (Medford : Polity Press, 2020)
"A pioneer of virtual reality technology on why AR is the 'next big thing in tech'"--
Slated as ‘the next big thing in tech', augmented reality promises to take the screen out of our hands and wrap it around the world via ‘smart spectacles'. As a pervasive, invisible interface between the world and our senses, AR offers unparalleled capacity to reveal hidden digital depths, but it also comes at a cost to our privacy, our property, and our reality.
Includes bibliographical references and index.
Keywords: Augmented reality; Virtual reality